2015
DOI: 10.1088/0957-4484/26/7/075701
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor to metal transition in bilayer phosphorene under normal compressive strain

Abstract: Abstract. Phosphorene, a two-dimensional (2D) analog of black phosphorous, has been a subject of immense interest recently, due to its high carrier mobilities and a tunable bandgap. So far, tunability has been predicted to be obtained with very high compressive/tensile in-plane strains, and vertical electric field, which are difficult to achieve experimentally. Here, we show using density functional theory based calculations the possibility of tuning electronic properties by applying normal compressive strain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…For example, the application of uniaxial stress can break the symmetry and enhance in-plane anisotropy. 72 Other effects include electron-phonon coupling enhancement, 73 superconductivity, 74 semiconductor to metal transition, 75 band gap modification, 15 and direct-indirect band gap transition 12 ( Fig. 5).…”
Section: Effects Of Stress and Mechanical Propertiesmentioning
confidence: 99%
“…For example, the application of uniaxial stress can break the symmetry and enhance in-plane anisotropy. 72 Other effects include electron-phonon coupling enhancement, 73 superconductivity, 74 semiconductor to metal transition, 75 band gap modification, 15 and direct-indirect band gap transition 12 ( Fig. 5).…”
Section: Effects Of Stress and Mechanical Propertiesmentioning
confidence: 99%
“…They are very sensitive to external perturbations, which may make them promising candidates for various types of sensor [96,[146][147][148][149][150]. The interband optical transitions of few-layer phosphorene cover a wide spectrum range from visible to midinfrared that is important for telecommunication and solar energy harvesting [132,151,152].…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…Recently a theoretical study by Manjanath et. al 35 reported a reversible semiconductor to metal transition in bilayer phosphorene by applying normal compressive strain. In another work, Xiang et al 31,36 reported colossal positive magneto-resistance in black phosphorus for P ≥ 1.2 GPa and observed a non-trivial π Berry phase from the Shubnikov-de Haas oscillation measurement.…”
Section: Introductionmentioning
confidence: 99%